The study of the stylistic components of the \"Hajme Sabz\" of Sohrab Sepehri - شیرزاد طایفی; لیلا کمالخانی (مطالعات زبانی و بلاغی)
“Sohrab Sepehri“ is a researcher, pensive and stylist artist .and The “Eight Book’ is the product of his thoughts, reflection and his interior and exterior movement.